Menstimulasi Pra Membaca Pada Anak Usia 4-5 Tahun di TK Islam Allam Pelem Watu Menganti Gresik Melalui Media Flashcard - Muawanah; Naning Yuliani (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This research was conducted to increase reading creativity with the help of flashcard media in children aged 4-5 years and can find out the role of teachers in developing pre-reading stimulation in children aged 4-5 years in Islamic Kindergarten Allam Pelem Watu Menganti Gresik through flashcard media. This study uses a descriptive approach. The subjects of this study were 10 children aged 4-5 years, 6 boys and 4 girls and 2 teachers of class A group. Researchers collected data through observation, interviews, and documentation. From the results, this study was able to improve aspects of the pre-reading development of children aged 4-5 years so that they developed very well. Judging from the results of observations in the field, the use of stimulating pre-reading through flashcard media to improve the pre-reading development of children aged 4-5 years is the use of the flashcard method equipped with interesting and varied pictures. This is evidenced from the results of the checklist on the assessment of pre-reading developmental aspects of group A children aged 4-5 years, that when using the story method and without using interesting and varied pictures, there are some children who still lack a sense of self-awareness, responsibility and prosocial behavior.